Effectiveness of Formative Evaluation on Mathematics Achievement - Acharya, Nara Hari (Educational Journal, 2023)
Assessment plays a major role in how students learn, their motivation to learn, and how teachers teach. So in this research I have intended the effectiveness of the formative evaluation with analyzing non-cognitive behavior of students of basic level in mathematics. The mixed method approach was administrated for the study. The data were collected from achievement test of experimental and control group of students, interview and classroom observation form. It was found that there is no significant difference between the achievement score pre-test and posttest of the control group. But there is significant difference between achievements of the experimental group i.e, is the score of posttest is better than the pretest. Furthermore, the students who were teaching with different formative assessment strategies are more active and creative during the classroom teaching rather than the control group.